Effects of the soft tissue artefact on the hip joint kinematics during unrestricted activities of daily living. (7th May 2020) - D'Isidoro, Fabio; Brockmann, Clara; Ferguson, Stephen J.
Abstract: Soft tissue artefact (STA) affects the kinematics retrieved with skin marker-based motion capture, and thus influences the outcomes of biomechanical models that rely on such kinematics. In order to be compensated for, the effects of STA must be characterized across a broad sample population and for different motion activities. In this study, the error introduced by STA on the kinematics of the hip joint and of its individual components, and on the location of the hip joint center (HJC) was quantified for fifteen THA subjects during overground gait, stair descent, chair rise and putting on socks. The error due to STA was computed as the difference between the kinematics measured with motion capture and those measured simultaneously with moving fluoroscopy, a STA-free X-ray technique. The main significant effects of STA were: underestimation of the hip range of motion for all four activities, underestimation of the flexion especially during phases of the motion with higher flexion, overestimation of the internal rotation, and lateral misplacement of the HJC mostly due to the functional calibration. The thigh contributed more to the STA error than the pelvis. The STA error of the thigh appeared to be correlated with the hip flexion angles, with a varying degree of linearity depending on the activity and on the phase of the motion cycle. Future kinematic-driven STA compensation models should take into account the non-linearity of the STA error and its dependency of the phase of the motion cycle.